Expression and Purification of Extracellular Solute-Binding Protein (ESBP) in Escherichia coli, the Extracellular Protein Derived from Bifidobacterium longum KACC 91563 - Song, Minyu (Food Sci Anim Resour, 2019)
Bifidobacterium longum KACC 91563 secretes family 5 extracellular solute-binding protein via extracellular vesicle. In our previous work, it was demonstrated that the protein effectively alleviated food allergy symptoms via mast cell specific apoptosis, and it has revealed a therapeutic potential of this protein in allergy treatment. In the present study, we cloned the gene encoding extracellular solute-binding protein of the strain into the histidine-tagged pET-28a(+) vector and transformed the resulting plasmid into the Escherichia coli strain BL21 (DE3). The histidine-tagged extracellular solute-binding protein expressed in the transformed cells was purified using Ni-NTA affinity column. To enhance the efficiency of the protein purification, three parameters were optimized; the host bacterial strain, the culturing and induction temperature, and the purification protocol. After the process, two liters of transformed culture produced 7.15 mg of the recombinant proteins. This is the first study describing the production of extracellular solute-binding protein of probiotic bacteria. Establishment of large-scale production strategy for the protein will further contribute to the development of functional foods and potential alternative treatments for allergies.